Implementation of “The Project to Strengthen the Profile of Pancasila Students (P5)” SLB Negeri P Theme "Bhinneka Tunggal Ika" Through Safari Activities to X Hamlet - Juhanaini, Juhanaini; Aulia Qisthi (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This research aims to determine the implementation of the Project for Strengthen the Profile of Pancasila Students (P5) of SLB Negeri P with the theme "Bhinneka Tunggal Ika" which is packaged through a safari activity to X Hamlet. This research uses a qualitative approach with a case study method carried out to see and observe the learning carried out. Data collection techniques use interviews and observation. The data analysis technique in this research uses three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research show that there are three stages in implementing P5, namely planning, implementation and evaluation. This research shows that there is a good impact on SLB Negeri P students and teachers as well as the residents of X Hamlet.